Surface-enhanced infrared spectroscopy using nanometer-sized gaps - Huck, Christian; Neubrech, Frank; Vogt, Jochen; Toma, Andrea; Gerbert, David; Katzmann, Julia; Härtling, Thomas; Pucci, Annemarie (ACS nano, 2014)
We report on the near-field coupling of individual gold nanoantennas arranged in tip-to-tip dimer configuration, leading to strong electromagnetic field enhancements in the infrared, which is of great interest for sensing applications such as surface-enhanced infrared spectroscopy. We quantitatively evaluated the enhancement of vibrational excitations of a 5 nm thick test layer of 4,4′-bis(N-carbazolyl)-1,1′-biphenyl as a function of different gap sizes. The dimers with the smallest gaps under investigation (∼3 nm) lead to more than 1 order of magnitude higher signal enhancement with respect to gaps of 50 nm width. The comparison of experimental data and finite-difference time-domain simulations reveals a nonperfect filling of the gaps with sizes below 10 nm, which means that morphological information on the nanoscale is obtained additionally to chemical information.